Cross-Cultural Adaptation and Psychometric Validation of the Functional Assertiveness Scale among Indonesian College Students - Nadine Salsabila Anandita; Fatma Kusuma Mahanani; Takashi Mitamura (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to adapt and evaluate the psychometric properties of the Indonesian version of the Functional Assertiveness Scale (FAS) (Mitamura, 2018). The scale was translated and culturally adapted following the International Test Commission Guidelines for Translating and Adapting Tests (Second Edition) (ITC, 2018), involving three translators, six expert reviewers, and 11 lay reviewers. A quantitative approach was employed, and the adapted instrument was administered to 303 Indonesian university students aged 18-23 years selected through convenience sampling. Construct validity was evaluated using Confirmatory Factor Analysis (CFA), reliability was assessed using Cronbach’s alpha coefficients, and measurement invariance across gender was examined using Multi-Group Confirmatory Factor Analysis (MG-CFA). The CFA supported the original 12-item two-factor structure, with satisfactory model fit (TLI = 0.951, CFI = 0.937, SRMR = 0.045, RMSEA = 0.051) after residual covariances were added in single-group CFA. Reliability coefficients were satisfactory for the Objective Effectiveness subscale (α = 0.803), the Pragmatic Politeness subscale (α = 0.713), and the total scale (α = 0.799). Furthermore, MG-CFA demonstrated strict measurement invariance across gender, indicating that the scale functions equivalently for male and female respondents. These findings provide evidence that the Indonesian version of the Functional Assertiveness Scale is a valid and reliable instrument for measuring functional assertiveness and supports its use in future psychological research and assessment in Indonesia.